Fiber in Diet Is Associated with Improvement of Glycated Hemoglobin and Lipid Profile in Mexican Patients with Type 2 Diabetes - Lubia Velázquez-López; Abril Violeta Muñoz-Torres; Carmen García-Peña; Mardia López-Alarcón; Sergio Islas-Andrade; Jorge Escobedo-de la Peña (Journal of Diabetes Research)
Objective. To assess the association of dietary fiber on current everyday diet and other dietary components with glycated hemoglobin levels (HbA1c), glucose, lipids profile, and body weight body weight, in patients with type 2 diabetes. Methods. A cross-sectional survey of 395 patients with type 2 diabetes was performed. HbA1c, fasting glucose, triglycerides, and lipids profile were measured. Weight, waist circumference, blood pressure, and body composition were measured. Everyday diet with a semiquantitative food frequency questionnaire was evaluated. ANOVA, Kruskal-Wallis, chi-square tests and multivariate logistic regression were used in statistical analysis. Results. Higher fiber intake was associated with a low HbA1c, high HDL-c levels, low weight, and waist circumference. The highest tertile of calories consumption was associated with a higher fasting glucose level and weight. The highest tertile of carbohydrate consumption was associated with a lower weight. The lowest tertile of total fat and saturated fat was associated with the highest tertile of HDL-c levels, and lower saturated fat intake was associated with lower weight (p<0.05). Conclusions. A higher content of fiber in the diet reduces HbA1c and triglycerides, while improving HDL-c levels. Increasing fiber consumption while lowering calorie consumption seems to be an appropriate strategy to reduce body weight and promote blood glucose control.